Long term carbon storage in seagrass meadows and saltmarshes in the Ria Formosa along a hydrodynamic gradient - Martins, Márcio Filipe Cabral (2017)
Identification, quantification and monetization of ecosystem services is key for current ecosystem management and policy making. Current estimates of global organic carbon stocks in seagrass meadows and saltmarshes suffer from overrepresentation of certain species and do not account for variation in carbon storage due to abiotic factors. Sediment cores were extracted in Zostera noltei and Spartina maritima habitats along a hydrodynamic gradient in the Ria Formosa, a location that was converted to a clam farm and an area colonized by Caulerpa prolifera. Vegetation at those locations was also described. Organic carbon storage, contribution of the main organic matter sources to the sediment and vegetation properties were analyzed. Relations to estimate organic carbon and total nitrogen using organic matter values were estimated and the possibility of using sediment color to estimate organic matter was investigated. Z. noltei and S. maritima both stored similar amounts of carbon, on average 2.2 times more than the clam farm. The effect of hydrodynamics was significant, with carbon storage capacities in Z. noltei and S. maritima increasing by a maximum factor of 2.08 and 3.44 (respectively), from the most exposed to most sheltered station. Suspended particulate organic matter and autochthonous organic matter were the major contributors to sedimentary organic matter, with a bigger contribution from the former in Z. noltei sediment. No significant differences in contributions were found along the hydrodynamic gradient. Organic carbon storage in Z. noltei and S. maritima fell below reported global means, with the difference becoming even more drastic in high hydrodynamics areas. Understanding carbon storage variation and increasing the diversity of conditions under which they are measured is a key point to increase accuracy of carbon stocks estimations both at a global and local scale.